White matter alterations in Parkinson's disease with normal cognition precede grey matter atrophy - Rektor, Ivan; Svátková, Alena; Vojtíšek, Lubomír; Zikmundová, Iva; Vaníček, Jirí; Király, András; Szabó, Nikoletta (PLoS One, 2018)
INTRODUCTION: While progressive MRI brain changes characterize advanced Parkinson's disease (PD), little has been discovered about structural alterations in the earliest phase of the disease, i.e. in patients with motor symptoms and with normal cognition. Our study aimed to detect grey matter (GM) and white matter (WM) changes in PD patients without cognitive impairment. METHODS: Twenty PD patients and twenty-one healthy controls (HC) were tested for attention, executive function, working memory, and visuospatial and language domains. High-resolution T1-weighted and 60 directional diffusion-weighted 3T MRI images were acquired. The cortical, deep GM and WM volumes and density, as well as the diffusion properties of WM, were calculated. Analyses were repeated on data flipped to the side of the disease origin. RESULTS: PD patients did not show any significant differences from HC in cognitive functioning or in brain volumes. Decreased GM intensity was found in the left superior parietal lobe in the right (p<0.02) and left (p<0.01) flipped data. The analysis of original, un-flipped data demonstrated elevated axial diffusivity (p<0.01) in the superior and anterior corona radiata, internal capsule, and external capsule in the left hemisphere of PD relative to HC, while higher mean and radial diffusivity were discovered in the right (p<0.02 and p<0.03, respectively) and left (p<0.02 and p<0.02, respectively) in the fronto-temporal WM utilizing flipped data. CONCLUSIONS: PD patients without cognitive impairment and GM atrophy demonstrated widespread alterations of WM microstructure. Thus, WM impairment in PD might be a sensitive sign preceding the neuronal loss in associated GM regions.
Keywords: bílá hmota; Male; šedá hmota; Middle Aged; progrese nemoci; magnetická rezonanční tomografie; atrofie; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; Disease Progression; Neuroimaging; Neuropsychological Tests; neurozobrazování; Atrophy; kognice; lidé; Gray Matter; ženské pohlaví; studie případů a kontrol; Humans; White Matter; neuropsychologické testy; Magnetic Resonance Imaging; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Cognition